Auxin‐mediated induction of GAL promoters by conditional degradation of Mig1p improves sesquiterpene production in Saccharomyces cerevisiae with engineered acetyl‐CoA synthesis. Issue 6 (9th September 2021) - Hayat, Irfan Farabi; Plan, Manuel; Ebert, Birgitta E.; Dumsday, Geoff; Vickers, Claudia E.; Peng, Bingyin
Summary: The yeast Saccharomyces cerevisiae uses the pyruvate dehydrogenase‐bypass for acetyl‐CoA biosynthesis. This relatively inefficient pathway limits production potential for acetyl‐CoA‐derived biochemical due to carbon loss and the cost of two high‐energy phosphate bonds per molecule of acetyl‐CoA. Here, we attempted to improve acetyl‐CoA production efficiency by introducing heterologous acetylating aldehyde dehydrogenase and phosphoketolase pathways for acetyl‐CoA synthesis to enhance production of the sesquiterpene trans ‐nerolidol. In addition, we introduced auxin‐mediated degradation of the glucose‐dependent repressor Mig1p to allow induced expression of GAL promoters on glucose so that production potential on glucose could be examined. The novel genes that we used to reconstruct the heterologous acetyl‐CoA pathways did not sufficiently complement the loss of endogenous acetyl‐CoA pathways, indicating that superior heterologous enzymes are necessary to establish fully functional synthetic acetyl‐CoA pathways and properly explore their potential for nerolidol synthesis. Notwithstanding this, nerolidol production was improved twofold to a titre of ˜ 900 mg l −1 in flask cultivation using a combination of heterologous acetyl‐CoA pathways and Mig1p degradation. Conditional Mig1p depletion is presented as a valuable strategy to improve the productivities in the strains engineered with GAL promoters‐controlled pathways when growing on glucose. Abstract : We attempted to improve acetyl‐CoA production efficiency by introducing heterologous acetylating aldehyde dehydrogenase and phosphoketolase pathways for acetyl‐CoA synthesis to enhance production of the sesquiterpene nerolidol. Conditional Mig1p depletion is presented as a valuable strategy to improve the productivities in the strains engineered with GAL promoters‐controlled pathways when growing on glucose.